Food environment and consumption of ultra-processed foods influencing food addiction in socially vulnerable women in Brazil - Luiz Gonzaga Ribeiro Silva-Neto; Nassib Bezerra Bueno; Camila Aparecida Borges; Risia Cristina Egito de Menezes; André Eduardo da Silva Júnior; Thays Lane Ferreira dos Santos; Telma Maria de Menezes Toledo Florêncio (Public Health Nutrition)
Abstract